Deglacial Tropical Atlantic subsurface warming links ocean circulation variability to the West African Monsoon. Issue 1 (December 2017) - Schmidt, Matthew; Chang, Ping; Parker, Andrew; Ji, Link; He, Feng
Abstract Multiple lines of evidence show that cold stadials in the North Atlantic were accompanied by both reductions in Atlantic Meridional Overturning Circulation (AMOC) and collapses of the West African Monsoon (WAM). Although records of terrestrial change identify abrupt WAM variability across the deglaciation, few studies show how ocean temperatures evolved across the deglaciation. To identify the mechanism linking AMOC to the WAM, we generated a new record of subsurface temperature variability over the last 21 kyr based on Mg/Ca ratios in a sub-thermocline dwelling planktonic foraminifera in an Eastern Equatorial Atlantic (EEA) sediment core from the Niger Delta. Our subsurface temperature record shows abrupt subsurface warming during both the Younger Dryas (YD) and Heinrich Event 1. We also conducted a new transient coupled ocean-atmosphere model simulation across the YD that better resolves the western boundary current dynamics and find a strong negative correlation between AMOC strength and EEA subsurface temperatures caused by changes in ocean circulation and rainfall responses that are consistent with the observed WAM change. Our combined proxy and modeling results provide the first evidence that an oceanic teleconnection between AMOC strength and subsurface temperature in the EEA impacted the intensity of the WAM on millennial time scales.